Avaliação do desempenho de wetlands horizontais subsuperficiais como pós-tratamento de efluentes de reatores UASB - Filipe Lima Dornelas (2008)
A system comprised by a UASB (Upflow Anaerobic Sludge Blanket) reactor followed by two horizontal subsurface-flow constructed wetlands in parallel was evaluated for the treatment of the wastewater generated in the city of Belo Horizonte, Brazil (50 inhabitants each unit). Oneunit was planted (Typha latifolia) and the other was unplanted. Influent and effluent samples were collected for a period of seven months.The final effluent had an excellent quality in terms of organic matter and suspended solids, but showed a lower capacity for removing nutrients. Mean effluent concentrations for the planted and unplanted units were, respectively: BOD: 15 and 19 mg/L; COD: 42 and 64 mg/L; TSS: 3 and 5 mg/L; TN: 27 and 33 mg/L; N-NH3: 25 and 29 mg/L; P Total: 1.2 and 1.5mg/L; Total Coliforms: 9,0 x 105 e 2,0 x 106 MPN/100 mL; E. coli: 1,3 x 105 e 4,6 x 105 MPN/100 mL. The planted wetland presented effluent concentrations and removal efficiencies significantly (Wilcoxon matched-pairs test) better than the unplanted unit for most constituents. The study shows that horizontal subsurface-flow constructed wetlands can effectively treat the effluent from UASB reactors, being capable of complying with most discharge standards for organic matter and suspended solids.